Research of mechanical components of the Malaysian army tank Alvis Scorpion 90 / Razman Marsoff Johar and Wan Zul Atfi Yusmar Wan Yusof - Johar, Razman Marsoff; Wan Yusof, Wan Zul Atfi Yusmar (Faculty of Mechanical Engineering, 1999)
Tank, a heavily armored, highly mobile vehicle possessing a large-caliber gun capable of delivering tremendous firepower. Generally, it is track laying vehicle travel on two endless belts, called tracks, one on each side. The main purpose of the tank is used in ground offensive combat. Thus, it is very crucial for the tank to have highly mobile capabilities especially during attacking as well as defensive. In order to have these capabilities, a lot of time, dedications, manpower and energy have been sacrificed for study, research and development, in order to keep on improving the mechanical and overall construction of the tank. Therefore, the main purpose of this project is to know and to study the mechanical components in a tank, and if possible, to relate it with the subjects that that have been taught in Mechanical Diploma Course in Mara University Of Technology. The main focus in this study will be the model of an Alvis Scorpion 90 tank, which is the main battle tank in the Malaysian Army. In addition to that, our purpose is also to give some ideas or suggestions to improve the capabilities of the existing Scorpion 90 in order to cope and to satisfy the needs and demands for the coming millennium.